Polymer‐Functionalized Mitochondrial Transplantation to Plaque Macrophages as a Therapeutic Strategy Targeting Atherosclerosis (Adv. Therap. 5/2022). Issue 5 (17th May 2022) - Liu, Haoran; Wu, Suhong; Lee, Hyunho; Baudo, Gherardo; Massaro, Matteo; Zhang, Aijun; Hamilton, Dale J.; Blanco, Elvin
Abstract : In article 2100232, Elvin Blanco and co‐workers demonstrate that polymer‐functionalized mitochondria delivered intravenously accumulate in atherosclerotic plaques, specifically in macrophages. Consequently, macrophages undergo a metabolic reprogramming away from glycolysis that hampers inflammatory processes and plaque progression. This work highlights the therapeutic potential of mitochondrial transplantation in diseases whose hallmarks include mitochondrial dysfunction and aberrant cell bioenergetics.